The Calahan Method for Parabolic Equations with Time-Dependent Coefficients (Journal of Computational Mathematics, 1987)
A modified Calahan method for parabolic equations with time-dependent coefficients is presented. It is shown that the convergence order is $O(h^{r+1}+k^3)$ while the convergence order obtained in [1] for a standard Calahan method is only $O(h^{r+1}+k^2)$.